A New Lossless Embedding Techniques Based on HDWT. Issue 1 (2nd January 2017) - Huang, Li-Chin; Feng, Tung-Huang; Hwang, Min-Shiang
ABSTRACT: Considering information security, reversible data hiding methods provide an efficient and simple way to prevent illegal accessing and unauthorized tampering. Adopting converted techniques, original images are going to be transferred to a collection of coefficients to be altered for embedding secret message. Then, the coefficients are converted to stego-images inversely. And stego-images are able to be a cover image to embed secrete message at the next stage. The horizontal operation of Haar digital wavelet transformation transfers images format from spatial domain to frequency domain in this paper. Then, decimal of coefficients will be altered for hiding secret bits. Finally, the modified coefficients are inversely transformed to stego-images. Our scheme has high peak signal to noise ratio (PSNR) when bits per pixel are near one bit. In this paper, we are concerned about data hiding for a special kind of image.